Existence of positive periodic solutions for higher order singular functional difference equations - Jacob Johnson; Lingju Kong; Michael Ruddy; Alexander Ruys De Perez (Electronic Journal of Qualitative Theory of Differential Equations, 2014)
We study a higher order singular functional difference equation on $\mathbb{Z}$. Sufficient conditions are obtained for the existence of at least one positive periodic solution of the equation. Our proof utilizes the nonlinear alternative of Leray-Schauder.